RRAM SPICE modeling with LT spice - Guan, Wenjiang (Nanyang Technological University, 2024)
This thesis conducts a thorough analysis and explanation based on two theoretical models from Stanford University and Peking University, implements and validates these models using LTspice software. The comparison reveals that building SPICE models through coding is more straightforward and practical, while parameter analysis suggests that the Peking University model is more comprehensive, although it is slightly less flexible.